(untitled) (Bangladesh Journal of Agriculture, 2023)
Gummosis in a Rain tree [Samanea saman (Jacq.) Merr.] is a new disease in Bangladesh. The prevalence of this disease is increasing over time. An exploratory survey was made to find out the extent of this disease in different areas of Bangladesh during 2017 and 2018. Infested samples of wood were collected to find out associated pathogens. After the isolation of the fungi in the Forest Pathology Laboratory of the Bangladesh Forest Research Institute, the optimal conditions for the growth of the pathogen was determined. Subsequently, the suitable control method was developed. It was found that the roadside plantation of Mongla Sadar Thana, Bagerhat district had the highest disease incidence and severity (42.93 and 54.38 %), and the lowest (12.63 and 18.34 %) was recorded at Satkhira Sadar Thana, Satkhira district, respectively. Lasiodiplodia theobromae [(Pat.) Griff. & Maubl)] was found associated with gummosis in the affected trees. The result of the pathogenicity test revealed that there was a similarity in symptoms that arise between artificial inoculation and natural symptoms in the field. The optimal condition of conidial germination, mycelial growth, and sporulation of L. theobromae was observed at pH 6-8, 90-95 RH, and 25-30°C temperature. The concentration of 2.5 % glucose and sucrose was the best for conidial germination, mycelial growth, and sporulation, and sucrose was better than glucose. PDA medium had the maximum mycelial growth (72.18 mm) and excellent sporulation, while the YEA medium had the lowest mycelial growth (59.19 mm) and poor sporulation. The fungicides Knowin (Carbendazim), ARBA (Carbendazim), and Autostin (Carbendazim) were found to completely inhibit pathogen mycelial growth and sporulation (100%) at 50, 100, and 150 mg/L concentrations. Furthermore, spraying these fungicides and the Bordeaux mixture at a rate of 2 % in the field resulted in the development of the smallest gummosis lesions. L. theobromae was a pathogen causing gummosis disease of rain tree, proven by morphology and Koch’s postulates. Different environmental and nutritional factors affect the growth and sporulation of the pathogen and the application of Knowin, ARBA, Autostin, and Bordeaux mixture at 2 % can help control the disease at the field level. Bangladesh J. Agri. 2022, 47(2): 78-96